(untitled) (Research, Society and Development, 2021)
The effect of incorporating of breadcrumbs, oatmeal and cassava starch on the physicochemical and sensorial parameters of low-fat lamb burgers were investigated. Seven treatments were prepared: control (CONT), 2% or 4% addition of breadcrumbs (BRE2 and BRE4), oatmeal flour (OAT2 and OAT4) and cassava flour (CAS2 and CAS4); and analyzed their physicochemical parameters (moisture, protein, fat, ash, carbohydrate, energy, water holding capacity and cooking loss). Furthermore, consumers evaluated the sensory acceptance (color, taste, texture, aroma and overall quality) and indicated their preference. The treatments affected the characteristics of the product (P<0.05), the highest values of fat (12.26%) carbohydrate (2.83%), energy (194.39Kcal/100g) and cooking loss (54.90%) were found in CAS2, CAS4, OAT4 and BRE2, respectively. CAS2 group improved the taste, while BRE4 improved the texture and along with CAS4 were the batches most preferred by consumers (18.8% and 21.5%, respectively). Breadcrumbs and cassava flour are most recommended for low-fat lamb burger production.